Alternative analysis of 6-Nitro BIPS behaviour based on factorial design - Wahid, Zaharah; Nadir, Najiah; Usman, Mustofa (Institute Mathematical Sciences, Universiti Putra Malaysia, 2016)
There is a growing interest in the area of designing and synthesis of functional dye molecules that can serve as molecular devices for sensors,photo-switching and signal transduction. Among photochromic compounds that could be used for such purpose are spiropyrans. This paper presents an alternative analysis of 6-nitro-1’,3’,3’-1-benzopyran-2, 2’] (6-Nitro BIPS) behavior due to the impact of solvent polarity, durations of ultraviolet(UV) exposure and dye concentration. Factorial design of experiments was used to study the impact of the three factors versus a response (absorbance). Analysis of variance (ANOVA)is employed to analyze the results. The results obtained highlighted that and solvent polarity are the most significant variables. In addition this study shows that the interaction effect between the concentration and solvent factors is essential for better interpretation of the experiments. The models are developed from ANOVA and the models fulfilled the assumptions of normality and independence variances.